SHOPPING TROLLEY TRACKING SYSTEM VIA SMS USING ULTRA HIGH FREQUENCY APPLICATION - Meor Said, Maizatul Alice; othman, mohd azlishah; Misran, Mohamad Harris; Sulaiman, Hamzah Asyrani; Ismail, Mohd Muzafar (2012)
This paper presents the function of Application Radio Frequency In Keeping Track Shopping Trolley Using GSM. The objective of develop this project is to create a solution that can help the shopping management that provide trolleys services for the costumers or users to reduce cost to their company arising from the missing trolleys and frequently considered stolen This system consists of receiver and transmitter, and technically this device uses radio frequency wave concept to operate. If one of the trolleys is out of range, turn on a buzzer and a red light at the same time at control room than using GSM will sent Short Message Service (SMS) to guard. This capability provides ease and safety to safety guard, to monitor the trolleys frequently used by costumers or users. The operating frequency used by the transmitter is about 100MHz to 2.45GHz which the receiver can detect accurately within 10 to 100 meters; even through a protective casing is covering the transmitters. This covering is also use to avoid the users damaging the transmitters and to provide protection to the assembly. This is to ensure the trolley always in range.